Characterisation of the Toxoplasma gondii tyrosine transporter and its phosphorylation by the calcium‐dependent protein kinase 3. Issue 5 (25th November 2018) - Wallbank, Bethan A.; Dominicus, Caia S.; Broncel, Malgorzata; Legrave, Nathalie; Kelly, Gavin; MacRae, James I.; Staines, Henry M.; Treeck, Moritz
Summary: Toxoplasma gondii parasites rapidly exit their host cell when exposed to calcium ionophores. Calcium‐dependent protein kinase 3 ( Tg CDPK3) was previously identified as a key mediator in this process, as Tg CDPK3 knockout (∆ cdpk3 ) parasites fail to egress in a timely manner. Phosphoproteomic analysis comparing WT with ∆ cdpk3 parasites revealed changes in the Tg CDPK3‐dependent phosphoproteome that included proteins important for regulating motility, but also metabolic enzymes, indicating that Tg CDPK3 controls processes beyond egress. Here we have investigated a predicted direct target of Tg CDPK3, ApiAT5‐3, a putative transporter of the major facilitator superfamily, and show that it is rapidly phosphorylated at serine 56 after induction of calcium signalling. Conditional knockout of apiAT5‐3 results in transcriptional upregulation of most ribosomal subunits, but no alternative transporters, and subsequent parasite death. Mutating the S56 to a non‐phosphorylatable alanine leads to a fitness cost, suggesting that phosphorylation of this residue is beneficial, albeit not essential, for tyrosine import. Using a combination of metabolomics and heterologous expression, we confirmed a primary role in tyrosine import for ApiAT5‐3. However, no significant differences in tyrosine import could be detected in phosphorylation site mutants showing that if tyrosine transport is affected by S56 phosphorylation, its regulatory role is subtle. Abstract : ApiAT5‐3, a 12‐transmembrane domain protein that localises to the periphery of the parasite, is responsible for the import of tyrosine, and is essential for parasite survival. Tg CDPK3 mediates phosphorylation (blue star) at the S56 residue and may be involved in the regulation of tyrosine uptake from the host.